(untitled) (Bangladesh Journal of Child Health, 2012)
Background: Congenital heart disease (CHD) is the most common congenital problem in children. In order to avoid complications, reduce mortality and for proper management early detection of congenital heart disease is of utmost importance. Objectives: The purpose of this study was to find out a single tertiary center experience in disease pattern of CHD among children with comparative analysis of past and present situation. Methods: This study was conducted over a period of 2 years from January 2008 to December 2009 prospectively and another 2 years data was collected from hospital records from January 1998 to December 1999 retrospectively on all patients with the confirmed diagnosis of CHD admitted in Dhaka Shishu Hospital to compare present and past status. Patients from 1st day of life to 12 years of age were included in the study. Results: Acyanotic heart diseases were commonly found both in past and present (75% and 78.5% respectively) and among them Ventricular Septal Defect (VSD) was found the most common CHD (32.7% and 26.9% respectively). Atrial Septal Defect (ASD) was found 2nd most common CHD (25.6% and 21.2% respectively). Only 11.9% CHD were diagnosed during neonatal period in the past whereas 27.6% were diagnosed in the recent time. Rare CHD were detected more frequently in recent time. Conclusion: VSD is the commonest non-cyanotic lesion whereas TOF is the commonest cyanotic lesion both in past and present, though their frequency reduced than before. Early detection and detection of rare CHD during recent time may reflect the advancement of diagnostic skill and facilities as well as awareness. DOI: http://dx.doi.org/10.3329/bjch.v34i2.10217 BJCH2010; 34(2): 51-55